A Phase I and Pharmacodynamic Study of the Histone deacetylase inhibitor Belinostat plus Azacitidine in Advanced Myeloid Neoplasia - Odenike, Olatoyosi (Invest New Drugs, 2014)
BACKGROUND: We hypothesized that targeting two mechanisms of epigenetic silencing would be additive or synergistic with regard to expression of specific target genes. The primary objective of the study was to establish the maximum tolerated dose (MTD) of belinostat in combination with a fixed dose of azacitidine (AZA). METHODS: In Part A of the study, patients received a fixed dose of AZA, with escalating doses of belinostat given on the same days 1–5, in a 28 day cycle. Part B was designed to evaluate the relative contribution of belinostat to the combination based on analysis of pharmacodynamic markers, and incorporated a design in which patients were randomized during cycle 1 to AZA alone, or the combination, at the maximally tolerated dose of belinostat. RESULTS: 56 patients with myeloid neoplasia were enrolled. Dose escalation was feasible in part A, up to 1000 mg/m(2) dose level of belinostat. In Part B, 18 patients were assessable for quantitative analysis of specific target genes. At day 5 of therapy, MDR1 was significantly up-regulated in the belinostat/AZA arm compared with AZA alone arm (p=0.0023). There were 18 responses among the 56 patients. CONCLUSIONS: The combination of belinostat and AZA is feasible and associated with clinical activity. The recommended phase II dose is 1000 mg/m(2) of belinostat plus 75 mg/m(2) of AZA on days 1–5, every 28 days. Upregulation in MDR1 was observed in the combination arm at day 5 compared with the AZA alone arm, suggesting a relative biologic contribution of belinostat to the combination.